Perbandingan kalimat yang ditulis oleh jurnalis yang menggunakan bahasa Inggris sebagai bahasa ibu dan jurnalis yang menggunakan bahasa Inggris sebagai bahasa asing: Teks yang ditulis oleh jurnalis asing dan jurnalis lokal - P.C. . Sudarmadi (e-LinguaTera, 2021)
News in magazines and newspapers function to give information to the readers. Information in the media is prepared by journalists who work for hunting the news from the source, and who write the information to be articles published in the media. The language used in this publication may vary from local language to international languages, such as the English language. English is a global language learned and used by many people around the world therefore, mass media using English as their platform will cover more readers than those using local language as their platforms. In this research, the writer wants to compare four news articles written by four different journalists from different publishers; they are Text-1 and Text-2 originally written by foreign journalists using English as their native language, then Text-3 and Text-4 written by domestic journalists using English as their foreign language. The aim of this research is to know whether there are significantly different between news written by journalists using English as their speakers and news written by journalists using English as their foreign language. This research is very important for the writer himself as he is responsible for teaching writing subjects for the students of the English Literature Program, Faculty of Social and Humanity, Buddhi Dharma University, Tangerang. This will also be useful for the readers who want to be news’ writers or journalists to improve their style in writing English sentences so that they sound more English and are easy to understand by the readers.